Dari Pesantren hingga Kurikulum Merdeka: Jejak Evolusi Kurikulum Pendidikan di Indonesia - Auliyah, Nilna Nariatul; Pratiwi, Safna Amalia; Jamil, Sabrun (AL-FIKRA, 2024)
Dari Pesantren hingga Kurikulum Merdeka: Jejak Evolusi Kurikulum Pendidikan di IndonesiaTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//